GREEN GOVERNANCE SEBAGAI REFLEKSI ETIKA DAN KINERJA KORPORASI MODERN - Putri, Hanifah Yaffa Eka; Sari, Shinta Permata (ITB AAS Indonesia Surakarta, 2025)
The increasingly competitive business environment requires companies to maintain sustainable financial performance through good corporate governance and environmentally friendly accounting practices. This study analyzes the effect of green accounting, institutional ownership, independent commissioners, and audit committee on financial performance in energy sector companies listed on the Indonesia Stock Exchange during 2022–2024. Using a quantitative method, purposive sampling of 182 data, and multiple linear regression analysis, the results show that green accounting, institutional ownership, and independent commissioners have effect on financial performance, while the audit committee has no effect on financial performance. Keywords : Financial Performance, Green Accounting, Institutional Ownership, Independent Commissioners, Audit Committee.